If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + 4) = 9(x + -2) Reorder the terms: 9(4 + x) = 9(x + -2) (4 * 9 + x * 9) = 9(x + -2) (36 + 9x) = 9(x + -2) Reorder the terms: 36 + 9x = 9(-2 + x) 36 + 9x = (-2 * 9 + x * 9) 36 + 9x = (-18 + 9x) Add '-9x' to each side of the equation. 36 + 9x + -9x = -18 + 9x + -9x Combine like terms: 9x + -9x = 0 36 + 0 = -18 + 9x + -9x 36 = -18 + 9x + -9x Combine like terms: 9x + -9x = 0 36 = -18 + 0 36 = -18 Solving 36 = -18 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 10a+7a+4= | | 9+-1= | | 2(3-4x)=30 | | -x-3=2 | | 13=5x+3 | | -4-3n+m^2= | | -3x-4x=11-10x | | -5x+14x-x= | | X^2-33x-280=0 | | -7(2x+3)=-34-8x+7x | | 2(1-2x)=14 | | -1+-3= | | 1x+6=7 | | 5a+7=17 | | -2+-1= | | 3n-7=5n+9 | | 4(6x+2)-5(x-2)=6x-54+x | | -1/2+(-1/3)= | | 155+90= | | 1*2= | | 3a^2+30a+63= | | 1.2*-5= | | X-1=1+x | | 5x-8=3x+5 | | 13=29-8x | | 9/20+1/5= | | 3z=-5.85 | | 2z=2.1 | | -9-0= | | 4[-5x+7-3(x+1)]=-5x+4 | | -4x+7+6x=13 | | t=5n+5v |